Immobilized two-dimensional colloidal crystal and manufacturing method thereof
Through resin immobilization technology, the problem that the structure of two-dimensional charged colloidal crystals is easily disordered during the drying process is solved. Through the combination of various colloidal particles, the versatility of the material is enhanced and its application potential is expanded.
Patent Information
- Application Number
- CN202380040850.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-18
- Filing Date
- 2023-05-11
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, two-dimensional charged colloidal crystals are prone to colloidal particles during drying due to capillary force, resulting in confusion in the crystal structure; at the same time, it is difficult for a single colloidal particle to set up multiple reflection or absorption bands, which limits the widespread use of their materials. .
By fixing the two -dimensional glue crystal resin to limit the movement of the colloidal particles to avoid structural confusion; at the same time, a two -dimensional gel crystal composed of multiple colloidal particles is used to ensure the stability and multifunctional nature of the crystal structure through the resin. Essence
The structure of the two -dimensional colloidal crystals is not easy to chaos during drying, and through the combination of multiple colloidal particles, the multifunctionality of the materials in reflection and transmission spectrums has expanded its application potential in various fields.
Smart Images

Figure CN119343177A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an immobilized two-dimensional colloidal crystal and a method for preparing the same. Background Art
[0002] Colloid refers to the state in which the dispersed phase is dispersed in the dispersion medium. When the dispersion medium is a liquid, it is called a colloidal dispersion. "Charged colloidal particles" with electric charges on the surface have electrostatic repulsion between particles. Therefore, if appropriate conditions are selected, they will spontaneously be spaced apart and arranged regularly in the dispersion of charged colloidal particles. This structure is called a charged colloidal crystal.
[0003] The inventors of the present invention have successfully formed two-dimensional charged colloidal crystals on a substrate from a liquid in which charged colloidal crystals are dispersed, and have applied for a patent (Patent Document 1). Two-dimensional charged colloidal crystals refer to a regularly arranged structure in which colloidal particles are arranged in a single layer on a plane at a distance due to electrostatic repulsion. Two-dimensional charged colloidal crystals are expected to be used as functional surfaces in various fields such as sensing detection, photonics, and plasmon optics. For example, two-dimensional colloidal crystals of gold particles are expected to be used in analytical chemistry, biochemistry, materials science, and medical diagnosis as sensing detection materials and surface enhanced Raman substrates using surface plasmons. In addition, various particles can be used to easily make structures with diffraction peaks in the ultraviolet region to the near-infrared region, so as a substitute for a two-dimensional diffraction grating, it is also useful in the optical field. Furthermore, the realization of functional electrodes using metal particles and efficient catalyst chips using semiconductor particles is also expected.
[0004] In the method for forming a two-dimensional charged colloidal crystal described in Patent Document 1, charged colloidal particles are self-organized to form a thermodynamically stable structure. Therefore, unlike photolithography, it has the advantage of not requiring precise processing technology. In addition, by selecting the diameter of the colloidal particles, it can be used as a photon material corresponding to various wavelengths.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-34543 Summary of the invention
[0008] However, in the method described in Patent Document 1, although two-dimensional charged colloidal crystals can be obtained in a state of contact with a liquid medium such as water, there is a problem that during the drying process, the colloidal particles approach each other due to capillary forces and aggregate, causing a disorder in the crystal structure.
[0009] Furthermore, even if two-dimensional charged colloidal crystals are used in contact with a liquid medium such as water, there is still a problem that since there is only one type of colloidal particles, it is difficult to set multiple reflection bands or absorption bands in the reflection and transmission spectra, making it difficult to use the material more widely.
[0010] The present invention is completed in view of the above-mentioned actual situation in the past, and aims to solve at least one of 1) providing a two-dimensional colloidal crystal whose crystal structure is not easily disordered and a method for producing the same, and 2) providing a two-dimensional colloidal crystal composed of multiple colloidal particles and a method for producing the same. DETAILED DESCRIPTION
[0011] In the immobilized two-dimensional colloidal crystal of the present invention, the colloidal crystal composed of a single layer is immobilized by a resin. Therefore, the movement of the colloidal particles constituting the two-dimensional colloidal crystal is restricted by the resin, and the crystal structure is not easily disturbed even when an external force is applied.
[0012] In the immobilized two-dimensional colloidal crystal of the present invention, the colloidal crystal may be formed on a substrate. In this way, the colloidal crystal formed on the substrate can be easily produced by immobilizing the colloidal crystal with a resin.
[0013] In addition, in the immobilized two-dimensional colloidal crystal of the present invention, a light-transmitting substrate may be used from the viewpoint of using it in the optical field, such as as a substitute for a two-dimensional diffraction grating.
[0014] There are no particular restrictions on the resin used to immobilize the colloidal crystals, and for example, general-purpose polymer resins such as acrylic resins, styrene resins, epoxy resins, polyurethane resins, and styrene resins, silicone resins, and biopolymers can be used. Among acrylic resins, polydialkylacrylamide is easily adsorbed on colloidal particles such as silica, and thus is easily immobilized, and can be particularly preferably used.
[0015] In addition, the type of colloidal particles constituting the colloidal crystals is not particularly limited, and inorganic particles or organic particles can be used. From the viewpoint of reducing the lattice defects of the colloidal crystals, the particle size of the colloidal particles is preferably as uniform as possible. Specifically, the coefficient of variation of the particle size is preferably 20% or less, more preferably 15% or less, further preferably 10% or less, and most preferably about 5% or less. It should be noted that the coefficient of variation (CV) of the particle size here refers to the value of (standard deviation of the particle size × 100 / average particle size).
[0016] In addition, when the immobilized two-dimensional colloidal crystal of the present invention is used as a material with high light transmittance such as a transmission-type diffraction grating, it is preferred that the refractive index of the resin and the refractive index of the light-transmitting substrate are as close as possible. For example, the value of (refractive index of the resin / refractive index of the light-transmitting substrate) is preferably in the range of 0.9 to 1.1, and more preferably in the range of 0.95 to 1.05.
[0017] In addition, two-dimensional colloidal crystals can be composed of multiple types of colloidal particles. In this way, multiple reflection bands or absorption bands can be set in the reflection and transmission spectra, and they can be used as materials more widely.
[0018] In addition, the colloidal crystal may have a crystal structure with 4-fold symmetry or 6-fold symmetry.
[0019] The immobilized two-dimensional colloidal crystals of the present invention can be produced by the following method.
[0020] That is, the method for manufacturing two-dimensional colloidal crystals of the present invention is characterized in that it comprises: a substrate preparation step of preparing a substrate having a surface charge; a colloidal crystal dispersion preparation step of preparing a charged colloidal crystal dispersion in which three-dimensional colloidal crystals composed of colloidal particles having a surface charge with a sign opposite to that of the surface charge of the above-mentioned substrate are dispersed in a dispersion medium; a colloidal crystal adsorption step of bringing the above-mentioned charged colloidal crystal dispersion into contact with the above-mentioned substrate, thereby causing the colloidal crystals to be adsorbed on the above-mentioned substrate; a cleaning step of cleaning the above-mentioned substrate on which the above-mentioned colloidal crystals are adsorbed with a cleaning liquid, thereby forming a two-dimensional colloidal crystal composed of a single layer on the above-mentioned substrate; and a fixation step of bringing the substrate on which the above-mentioned two-dimensional colloidal crystals are formed into contact with a resin solution and then fixing the two-dimensional colloidal crystals by drying the resin solution.
[0021] In addition, after the immobilization step, the crystal structure of the immobilized two-dimensional colloidal crystal can be strengthened so as not to be disturbed by further polymerizing the polymerizable monomer on the immobilized two-dimensional colloidal crystal. As the polymerizable monomer, a monomer that polymerizes by light or a monomer that polymerizes by heat can be used.
[0022] In the method for manufacturing colloidal crystals of the present invention, by performing a second colloidal particle adsorption step of bringing the substrate formed with the above-mentioned two-dimensional colloidal crystal into contact with a second colloidal particle dispersion in which second colloidal particles different in type from the above-mentioned colloidal particles are dispersed in a dispersion medium after the above-mentioned cleaning step, and a cleaning step of cleaning the substrate adsorbed with the above-mentioned second colloidal particles, and then performing the above-mentioned immobilization step, it is also possible to form a fixed two-dimensional colloidal crystal in which the two-dimensional colloidal crystal composed of two types of colloidal particles is fixed.
[0023] Here, “immobilized two-dimensional colloidal crystal in which two-dimensional colloidal crystals composed of two types of colloidal particles are immobilized” means that the two types of colloidal particles respectively form crystal lattices of the two-dimensional colloidal crystal, and one of the colloidal particles of the other crystal lattice is located at the center of these crystal lattices.
[0024] It should be noted that after the cleaning step, by further contacting the substrate with a third colloidal dispersion in which third colloidal particles are dispersed, an immobilized two-dimensional colloidal crystal in which third colloidal particles are further adsorbed in the gaps between the two types of colloidal particles already adsorbed on the substrate can be produced. In addition, by further repeating the colloidal particle adsorption step and the cleaning step, an immobilized two-dimensional colloidal crystal composed of four or more types of colloidal particles can be produced.
[0025] In addition, in the two-dimensional colloidal crystal of the present invention, a plurality of colloidal particles form a colloidal crystal composed of a single layer, so that a plurality of reflection bands or absorption bands can be provided in the reflection and transmission spectra, and the two-dimensional colloidal crystal can be more widely used as a material.
[0026] In addition, the two-dimensional colloidal crystal may have a crystal structure with four-fold symmetry or six-fold symmetry.
[0027] The two-dimensional colloidal crystal of the present invention can be produced by the following method.
[0028] That is, the method for producing a two-dimensional colloidal crystal is characterized by performing the following steps:
[0029] A substrate preparation step of preparing a substrate having a surface charge;
[0030] a colloidal crystal dispersion preparation step of preparing a charged colloidal crystal dispersion in which three-dimensional colloidal crystals composed of first colloidal particles having a surface charge of opposite sign to that of the surface charge of the substrate are dispersed in a dispersion medium;
[0031] a colloidal crystal adsorption step of bringing the charged colloidal crystal dispersion into contact with the substrate, thereby adsorbing the colloidal crystals on the substrate;
[0032] A cleaning step of cleaning the substrate on which the colloidal crystal is adsorbed with a cleaning liquid to form a two-dimensional colloidal crystal consisting of a single layer on the substrate;
[0033] a colloidal particle adsorption step, after the cleaning step, contacting the substrate on which the two-dimensional colloidal crystal is formed with a colloidal particle dispersion in which second colloidal particles of a different type from the first colloidal particles are dispersed in a dispersion medium;
[0034] The second cleaning step is to clean the substrate on which the second colloidal particles are adsorbed.
[0035] It should be noted that after the second cleaning step, by further contacting the substrate with a third colloidal dispersion in which third colloidal particles are dispersed, a two-dimensional colloidal crystal in which third colloidal particles are further adsorbed in the gaps between the two types of colloidal particles already adsorbed on the substrate can be formed. In addition, by further repeating the colloidal particle adsorption step and the cleaning step, a two-dimensional colloidal crystal composed of four or more types of colloidal particles can be formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 (a) is a schematic cross-sectional view and (b) and (c) are schematic plan views of the two-dimensional colloidal crystal according to Embodiment 1.
[0037] Figure 2 This is a process diagram for producing fixed two-dimensional colloidal crystals with six-fold symmetry.
[0038] Figure 3 This is a schematic cross-sectional view of a device for growing colloidal crystals from one end side using a diffusion phenomenon in Embodiment 2.
[0039] Figure 4 This is a process diagram for producing fixed two-dimensional colloidal crystals with four-fold symmetry.
[0040] Figure 5 Schematic plan view and schematic cross-sectional view of a colloidal crystal (a) having a 4-fold symmetric crystal structure and a colloidal crystal (b) having a 6-fold symmetric crystal structure.
[0041] Figure 6 It is a graph showing the relationship between the dimension ratio d and the volume fraction.
[0042] Figure 7 This is a process diagram showing a method for producing immobilized two-dimensional colloidal crystals according to the third embodiment.
[0043] Figure 8 These are optical microscope photographs of the immobilized two-dimensional colloidal crystals of Examples 1 and 2 and Comparative Example 1.
[0044] Fig. 9 This is a diagram of the radial distribution function g(r) obtained from the optical microscope photographs of Example 1 before and after drying.
[0045] Fig.10 These are photographs of the appearance of Example 1 before and after drying and Comparative Example 1 after drying.
[0046] Fig.11 These are a photograph (a) of the appearance of the immobilized two-dimensional colloidal crystals of Example 3 and an optical microscope photograph (b).
[0047] Fig.12 is a schematic diagram of an apparatus used in the laser diffraction method.
[0048] Fig.13 This is a projection photograph of the laser diffraction pattern of the immobilized two-dimensional colloidal crystals of Example 2.
[0049] Fig.14 It is a schematic partial cross-sectional view of a cell for preparing colloidal crystals.
[0050] Fig.15 This is an optical microscope photograph of the two-dimensional colloidal crystal of Example 4 (before immobilization).
[0051] Fig.16 This is an optical microscope photograph of the two-dimensional colloidal crystal of Example 4 (after immobilization).
[0052] Fig.17 This is an optical microscope photograph of the two-dimensional colloidal crystal of Example 5 (after PDMA immobilization).
[0053] Fig.18 This is an optical microscope photograph of the two-dimensional colloidal crystal of Example 5 (after PDMA immobilization).
[0054] Fig.19 This is an optical microscope photograph of the two-dimensional colloidal crystal of Example 6-1 (before PDMA immobilization).
[0055] Fig. 20 This is an optical microscope photograph of the two-dimensional colloidal crystal of Example 6-1 (after PDMA immobilization).
[0056] Fig.21 These are optical microscope photographs of the two-dimensional colloidal crystals of Example 9 ((a) before immobilization, (b) after immobilization based on PEG, and (c) after immobilization based on PEG and polyvinylmorpholine).
[0057] Fig. 22 These are optical microscope photographs of the two-dimensional colloidal crystals of Example 10 ((a) after immobilization based on PEG, (b) after immobilization based on PEG and polyvinylmorpholine).
[0058] Fig.23 These are optical microscope photographs of the two-dimensional colloidal crystals of Example 11 ((a) before immobilization, (b) after immobilization using Pluronic (registered trademark)).
[0059] Fig.24 This is an optical microscope photograph of the two-dimensional colloidal crystal of Example 12 (after being immobilized by Pluronic (registered trademark)).
[0060] <Implementation method 1>
[0061] Regarding the immobilized two-dimensional colloidal crystal of embodiment 1, Figure 1 As shown in (a), colloidal particles 2 forming a two-dimensional colloidal crystal composed of a single layer exist on a substrate 1, and the colloidal particles 2 are immobilized by a resin 3. Therefore, the movement of the colloidal particles 2 is prevented by the resin 3, and the crystal structure of the two-dimensional colloidal crystal is not easily disturbed. It should be noted that even in a state where the colloidal particles 2 and the resin 3 are peeled off from the substrate 1, the immobilized two-dimensional colloidal crystal of the present invention is obtained.
[0062] As a type of two-dimensional colloidal crystals, Figure 1 As shown in (b), it can be a crystal structure of a face-centered cubic lattice (FCC) with a (111) plane orientation and a six-fold symmetric pattern, such as Figure 1 As shown in (c), a crystal structure having a four-fold symmetric pattern with a (100) plane orientation of a face-centered cubic lattice (FCC) may also be used.
[0063] The material of substrate 1 is not particularly limited, for example, ceramic substrates, plastic substrates, metal substrates, etc. such as glass plates and alumina plates can be used. In addition, the material of colloidal particles 2 constituting colloidal crystals can be used as long as it has a positive or negative surface charge in a dispersion medium. For example, particles constituting inorganic matter (such as SiO2 particles, TiO2 particles, alumina particles, etc.) and particles constituting organic matter (such as polystyrene particles, acrylic polymer particles, etc.) and particles after these particles are coated with metal (such as SiO2 particles after being coated with metal, etc.) can be cited. In addition, metal particles (such as precious metal particles such as Au particles, Pt particles, Pd particles, rhodium particles, iridium particles, ruthenium particles, osmium particles, rhenium particles, Ag particles, Cu particles, etc.) can also be used.
[0064] In addition, in order to adjust the surface charge of the colloidal particles, the surface can be modified by a chemical modifier such as a silane coupling agent. As for the dispersion of the colloidal particles, commercially available colloidal particles can be dispersed in an appropriate dispersion medium such as water, inorganic particles synthesized by a sol-gel method, or particles of relatively uniform size polymerized by emulsion polymerization of monomers such as styrene can be used as colloidal particles.
[0065] As the dispersion medium, water is cited as an example, but liquids other than water may also be used. For example, formamides (such as dimethylformamide) and alcohols (such as ethylene glycol) may be used. A mixed solution of these substances and water may also be used.
[0066] In addition, the resin 3 used to fix the colloidal particles 2 can be any resin that is soluble in or dispersed in the dispersion medium, for example, general-purpose polymer resins such as acrylic resins, styrene resins, epoxy resins, and urethane resins, silicone resins, biopolymers, etc. can be used.
[0067] <Implementation method 2>
[0068] The immobilized two-dimensional colloidal crystal of Embodiment 2 has a crystal structure of six-fold symmetric pattern and is composed of a single layer oriented on the (111) plane of a face-centered cubic lattice (FCC) (see Figure 1 (b)). This immobilized two-dimensional colloidal crystal can be Figure 2 The process shown is used to manufacture.
[0069] (Substrate preparation step S1)
[0070] A substrate 1 made of glass, ceramics, plastic, etc. is prepared. The substrate 1 needs to have a positive or negative surface charge in the dispersion. In order to make the surface charge of the substrate positive or negative, amino groups, sulfonic acid groups, etc. can be introduced into the surface of the substrate by a chemical modifier.
[0071] (Colloidal crystal dispersion preparation step S2)
[0072] On the other hand, a charged colloidal crystal dispersion is prepared in which three-dimensional charged colloidal crystals are dispersed in a dispersion medium. The colloidal particles constituting the charged colloidal crystals need to have a surface charge with a sign opposite to that of the surface charge of the substrate 1. In order to make the surface charge of the colloidal particles positive or negative, amino groups or the like can be introduced on the surface of the colloidal particles by a chemical modifier.
[0073] (Colloidal crystal adsorption step S3)
[0074] By bringing the charged colloidal crystal dispersion prepared as described above into contact with the substrate 1, the three-dimensional charged colloidal crystals 4 with six-fold symmetry are adsorbed to the substrate 1 by electrostatic attraction. The contact method is not particularly limited, and examples thereof include a method of dripping the charged colloidal crystal dispersion on the substrate 1 or immersing the substrate in the charged colloidal crystal dispersion.
[0075] (Cleaning Step S4)
[0076] Then, the substrate 1 is cleaned with a cleaning solution. The six-fold symmetric three-dimensional charged colloidal crystals 4 adsorbed on the substrate 1 through this process are washed away until only one layer remains on the substrate 1. The reason why only one layer remains on the substrate is that the colloidal particles 2 having a surface charge opposite to that of the substrate 1 are strongly adsorbed to the substrate 1 by electrostatic attraction.
[0077] (Fixation Step S5)
[0078] Then, the substrate 1 on which the two-dimensional colloidal crystal with six-fold symmetry is formed is brought into contact with a solution of a resin composed of a polymer (hereinafter referred to as a "resin solution"). As a result, the resin 3 is adsorbed on the substrate 1 and the colloidal particles 2. Furthermore, by drying the resin solution, the resin 3 is entangled with the colloidal particles 2 and the substrate 1, and is then firmly fixed. In this way, an immobilized two-dimensional colloidal crystal of embodiment 2 having a crystal structure with six-fold symmetry can be obtained.
[0079] It should be noted that in the colloidal crystal adsorption step S3 of the second embodiment, the method disclosed in Patent Document 1 can be used. Figure 3 As shown, a charged colloidal dispersion liquid 6 is filled in the gap between two opposing substrates 5a and b, and a charged colloidal crystal is crystallized by diffusing a charge preparation liquid 7 from one end side to form a charged colloidal crystal dispersion liquid 8. Here, the charge preparation liquid 7 refers to a liquid that can crystallize the charged colloidal particles in the charged colloidal dispersion liquid 6. In this way, by gradually growing the crystal from one end side of the gap using the diffusion phenomenon, a charged colloidal crystal with few lattice defects is crystallized.
[0080] The charge preparation liquid 7 is not particularly limited as long as it is a liquid that can crystallize the colloidal particles in the charged colloidal dispersion 6. Examples thereof include 1) surfactants such as anionic surfactant solutions, cationic surfactant solutions, nonionic surfactant solutions, and amphoteric surfactant solutions; 2) acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and carboxylic acids; 3) carbonate alkalis such as sodium carbonate, bicarbonate alkalis such as sodium bicarbonate, hydroxide alkalis such as sodium hydroxide, ammonia water, amines, and pyridine.
[0081] <Implementation method 3>
[0082] The immobilized two-dimensional colloidal crystal of Embodiment 3 has a crystal structure with four-fold symmetry (Four-fold Symmetric Pattern) and is composed of a single layer of (100) planes of FCC (face-centered cubic structure) (see Figure 1 (c)). The immobilized two-dimensional colloidal crystals can be Figure 4 The process shown is used to manufacture the product. The details are described below.
[0083] (Substrate Preparation Step S11)
[0084] Prepare a substrate 11 and a counter plate 12 made of glass, ceramic, plastic, etc. The substrate 11 needs to have a positive or negative surface charge in the dispersion. In order to make the surface charge of the substrate 11 positive or negative, amino groups, sulfonic acid groups, hydroxyl groups, etc. can be introduced on the surface by a chemical modifier.
[0085] (Colloidal Crystal Dispersion Liquid Preparation Step S12)
[0086] A charged colloidal crystal dispersion 14 in which three-dimensional colloidal crystals are dispersed in a dispersion medium is prepared. The colloidal particles constituting the charged colloidal crystals have a surface charge of opposite sign to the surface charge of the substrate 11. In order to make the surface charge of the colloidal particles positive or negative, amino groups or the like can be introduced into the surface of the colloidal particles by a chemical modifier.
[0087] (Colloidal crystal adsorption step S13)
[0088] After the charged colloidal crystal dispersion is dropped onto the substrate 11 (or the opposing plate 12), the opposing plate 12 (or the substrate 11) is stacked on top of it with a predetermined gap (see Figure 4 (a)) In order to set the interval between the substrate 11 and the opposing plate 12 to a predetermined interval, a spacer composed of a sphere with a predetermined radius and a plate with a predetermined thickness may be inserted between the substrate 11 and the opposing plate 12.
[0089] As time goes by, charged colloidal crystals ( Figure 4 (b)). In this case, the type of charged colloidal crystal formed varies according to the ratio of the distance (gap) h between the substrate 11 and the opposing plate 12 and the particle size (=2a) of the colloidal particles. Therefore, by controlling the distance (gap) h between the substrate 11 and the opposing plate 12, it is possible to obtain a selectively immobilized two-dimensional colloidal crystal having a crystal structure with four-fold symmetry.
[0090] This content can be derived from theoretical calculations. That is, assuming that the colloidal particles are rigid bodies, the density of colloidal particles in the confined space is assumed to be the largest in the (111) or (100) plane of the FCC structure. In addition, the interaction between colloidal particles only considers the potential energy of the rigid sphere, and as shown in formula (1), the pressure p is approximately the high-pressure limit that depends only on the size of the gap h.
[0091] [Formula 1]
[0092]
[0093] Here, g is the acceleration due to gravity, Δμ is the density difference between the colloidal particles and the dispersion medium, and ρ is the volume fraction of the colloidal particles. In this model, geometric calculations are performed on the crystal structure with four-fold symmetry and the crystal structure with six-fold symmetry to find the volume fraction. The distance between particles is set to r, the radius of the colloidal particle is set to a, and d = r / 2a. The schematic diagram of the crystal structure with four-fold symmetry is shown in Figure 5(a) In the same layer, when the distance between particles is greater than the particle size, particles in different layers are in contact, but particles in the same layer are not in contact with each other. In the same layer, when the distance between particles is equal to the particle size, the maximum filling rate of the colloidal particles obtained by the following formula (2) is 0.74.
[0094] [Formula 2]
[0095]
[0096] Here, □ represents a crystal structure having four-fold symmetry. As a result, the volume fraction ρn□ of colloidal particles when a crystal structure having four-fold symmetry is formed can be obtained by the following formula (3).
[0097] [Formula 3]
[0098]
[0099] Similarly, in a crystal structure with six-fold symmetry, in the same layer, when the interparticle distance is greater than the colloidal particle diameter, the colloidal particles of different layers are in contact, but the particles of the same layer do not contact each other ( Figure 5 (b)). In the same layer, when the interparticle distance = the colloidal particle diameter, d_(n△) is expressed by the following formula (4). Here, △ represents a crystal structure with six-fold symmetry.
[0100] [Formula 4]
[0101]
[0102] As a result, the volume fraction ρn△ of the colloidal particles when a crystal structure with six-fold symmetry is formed can be calculated using the following formula (5).
[0103] [Formula 5]
[0104]
[0105] exist Figure 6A graph is shown in which the size ratio d and the volume fraction are obtained from formula (3) and formula (5) (the dashed line with fine intervals represents the change in volume fraction of d relative to the crystal structure with four-fold symmetry, and the dashed line with thick intervals represents the change in volume fraction of d relative to the crystal structure with six-fold symmetry). The greater the particle density of the crystal structure, the more stable the crystal structure exists. Therefore, by dividing between the crystal structure with four-fold symmetry and the crystal structure with six-fold symmetry and at the point where the size relationship of the density of the colloidal particles changes, a phase diagram can be obtained. That is, it can be seen that as the value of h / 2a increases, the phase transition is carried out in the order of a crystal structure with six-fold symmetry composed of two layers (2△) → a crystal structure with four-fold symmetry composed of three layers (3□) → a crystal structure with six-fold symmetry composed of three layers (3△) → a crystal structure with four-fold symmetry composed of four layers (4□) → a crystal structure with six-fold symmetry composed of four layers (4△).
[0106] Based on the above results, the crystal structure of the colloidal crystal can be made into a crystal structure with four-fold symmetry or a crystal structure with six-fold symmetry by controlling the distance between the substrate 1 and the opposing plate 2. It should be noted that even if the substrate 11 and the opposing plate 12 are not parallel but tilted or the substrate 11 and the opposing plate 12 are deflected, the value of h / 2a varies depending on the location, and a crystal structure with four-fold symmetry can be partially formed.
[0107] It should be noted that the surface charge of the colloidal particles varies depending on the presence of trace salts (ionic impurities) in the dispersion medium. Therefore, when preparing a dispersion of colloidal particles, it is preferred that the dispersion medium be fully desalinated in advance. For example, when using water, the purified water is first dialyzed until the conductivity of the water used is equal to the value before use, and then the ion exchange resin (mixed bed of cation and anion exchange resin) that has been fully cleaned coexists with the sample and is maintained for at least 1 week, thereby performing desalination purification.
[0108] However, after desalting and purification in this manner, colloidal crystals may be crystallized by adding salts in advance and then performing desalting.
[0109] In addition, it is preferred to consider the particle size and distribution of the colloidal particles. The particle size of the colloidal particles is preferably less than 2000nm, and more preferably less than 1000nm. This is because it is difficult to be affected by Brownian motion and difficult to cause self-organized colloidal crystallization in the case of colloidal particles with a large particle size exceeding 2000nm. In addition, with regard to particles with a large specific gravity, it is because they are easy to settle due to the influence of gravity, and the stability of the dispersion of the colloidal particles deteriorates. In addition, the coefficient of variation of the particle size of the colloidal particles is preferably (i.e., the value obtained by dividing the standard deviation of the particle size by the average particle size) within 20%, more preferably less than 10%, and most preferably less than 5%. This is because if the coefficient of variation of the particle size becomes large, it is difficult for the colloidal crystals to crystallize, the lattice defects and inhomogeneity of the colloidal crystals increase, and it is difficult to obtain high-quality colloidal crystals.
[0110] (Cleaning Step S14)
[0111] In this way, charged colloidal crystals with a 4-fold symmetric crystal structure are electrostatically adsorbed (refer to Figure 4 (c)). As a method for electrostatic adsorption, the surface of the substrate 11 or the colloidal particles 13 can be modified with a silane coupling agent having an amino group, and a base such as NaOH, sodium bicarbonate, and sodium carbonate is added to the dispersion medium. The substrate 11 and the opposing plate 12 are immersed in water, thereby removing the cations between the substrate 11 and the opposing plate 12 by diffusion and convection. By removing the cations, the pH of the dispersion medium decreases, the amino groups are ionized, and the surface charge becomes positive. Therefore, the colloidal particles 13 are adsorbed on the substrate 11 due to electrostatic attraction. In this way, the charged colloidal crystals with a 4-fold symmetric crystal structure are adsorbed on the substrate 11 due to electrostatic attraction, and do not move even when immersed in pure water and are stably fixed. It should be noted that if an ion exchange resin is added to the immersion water, the removal of cations can be promoted.
[0112] (Fixation Step S15)
[0113] Finally, the substrate 11 formed with the two-dimensional colloidal crystal of four-fold symmetry is brought into contact with the resin solution. As a result, the resin 15 is adsorbed on the substrate 11 and the colloidal particles 13, and the two-dimensional colloidal crystal of four-fold symmetry is fixed. Furthermore, by drying the resin solution, the resin 14 is entangled with the two-dimensional colloidal crystal of four-fold symmetry and the substrate 11 and is firmly fixed. In this way, the fixed two-dimensional colloidal crystal of embodiment 3 having a crystal structure of four-fold symmetry can be obtained.
[0114] <Implementation method 4>
[0115] The immobilized two-dimensional colloidal crystal of the fourth embodiment is an immobilized two-dimensional colloidal crystal composed of two types of colloidal particles 22 and 23, which can be Figure 7The process shown is used to manufacture.
[0116] First, the substrate preparation step S21, the first colloidal crystal dispersion preparation step S22, the colloidal crystal adsorption step S23, and the cleaning step S24 are performed in the same manner as in Embodiment 2. In the first colloidal crystal dispersion preparation step S22, the concentration of the colloidal particles in the dispersion medium is controlled to be a predetermined concentration. Here, the predetermined concentration means that the two types of colloidal particles 22 and 23 form a lattice of a two-dimensional colloidal crystal, respectively, and are controlled so that one of the colloidal particles of the other lattice is located at the center of these lattices.
[0117] Next, the second colloidal particle dispersion preparation step S25, the colloidal crystal adsorption step S26, and the cleaning step S27 are further performed in the same manner. The colloidal particles 23 used in the second colloidal particle dispersion preparation step S25 are different from the colloidal particles 22 used in the first colloidal crystal dispersion preparation step S22 in particle size and / or material. It should be noted that the colloidal particles 23 used in the second colloidal particle dispersion preparation step S25 do not need to be colloidally crystallized.
[0118] Finally, as the immobilization step S28, after the substrate 21 is brought into contact with the resin solution, the resin solution is dried so that the resin 24 is entangled with the two-dimensional colloidal crystal composed of the colloidal particles 22 and the colloidal particles 23 and the substrate 21 and is firmly immobilized. In this way, an immobilized two-dimensional colloidal crystal 25 composed of two types of colloidal particles 22 and 23 can be obtained.
[0119] Example
[0120] <Immobilization of two-dimensional colloidal crystals having a crystal structure with six-fold symmetry>
[0121] (Example 1, Example 2 and Comparative Example 1)
[0122] Substrate preparation process
[0123] The surface of a cover glass for an optical microscope (manufactured by Matsunami Glass Industries, Ltd.) was modified with a silane coupling agent (3-aminopropyltrimethoxysilane), and a cover glass having a positive surface charge was obtained by introducing aminopropyl groups into the glass surface. A recess was provided by placing a silicone resin sheet (5 mm thick) having a hole of 1 cm×1 cm on the cover glass.
[0124] ·Colloidal crystal dispersion preparation process
[0125] A 6 vol.% aqueous dispersion of silica particles (KE-P100 manufactured by Nippon Shokubai Co., Ltd., particle size d=1060 nm) was prepared, and desalination was performed by adding an ion exchange resin (AG501-X8(D) manufactured by BioRad Co., Ltd., 20-50 sieve) to obtain an aqueous dispersion of three-dimensional charged colloidal crystals of silica particles regularly arranged in water due to electrostatic repulsion.
[0126] ·Colloid crystal adsorption process
[0127] An aqueous dispersion of three-dimensional charged colloidal crystals is poured into the recess of the cover glass.
[0128] Cleaning process
[0129] Then, after the recessed portion was washed with Milli-Q water, about 200 μL of Milli-Q water remained.
[0130] Immobilization process
[0131] Furthermore, 500 μL of an aqueous solution of polydimethylacrylamide (PDMA, molecular weight 144,000, synthesized by free radical polymerization) of a specified concentration was added to the concave portion and mixed with a pipette. Then, the water was evaporated by drying in an oven at 40°C overnight to obtain the immobilized two-dimensional colloidal crystals of Examples 1 and 2. It should be noted that the amount of PDMA added was 1.25 mg / cm in Example 1. 2 In Example 2, 0.1 mg / cm 2 In addition, the same operation was performed for the case where PDMA was not added as Comparative Example 1.
[0132] -evaluate-
[0133] The immobilized two-dimensional colloidal crystals of Examples 1 and 2 and Comparative Example 1 obtained as described above were observed from the back side of the cover glass using an inverted optical microscope. The results are shown in Figure 8 . It can be seen that in Example 1, before drying, the silica particles formed two-dimensional colloidal crystals with six-fold symmetry, and even after drying, the crystal structure remained unchanged without disorder. In addition, it can be seen that even for Example 2, although there was some disorder in the crystal structure after drying, the two-dimensional colloidal crystals with six-fold symmetry were maintained. In contrast, in Comparative Example 1 in which PDMA was not added, it was confirmed that the silica particles agglomerated and the crystal structure was disordered due to drying. The reason is that capillary attraction acts between the silica particles during the drying process, and the particles agglomerate with each other.
[0134] In addition, by performing image processing on the microscope photographs before and after drying of Example 1, the radial distribution function g(r) (r is the center distance between particles) was obtained. The results are shown in Fig. 9 The average interparticle distance obtained from the first peak position of g(r) was 1.55±0.06μm before drying and 1.54±0.03μm after drying, which was consistent within the range of measurement error. This shows that the crystal structure can be maintained even after drying.
[0135] It should be noted that if the thickness of the PDMA layer is calculated by taking the specific gravity of PDMA as the value of 0.964 as a single substance, it becomes 13 μm in Example 1, which is sufficiently thicker than the particle size of the silica particles (approximately 1 μm), and becomes 1.04 μm in Example 2, which is approximately the same as the particle size of the silica particles.
[0136] The appearance photos of Example 1 before and after drying and Comparative Example 1 after drying are shown in Fig.10 In Example 1, structural colors were observed before and after drying. In contrast, in Comparative Example 1, no structural colors were observed after drying. The results are as follows. That is, in the two-dimensional colloidal crystal of Example 1, Figure 8 As described above, the crystal structure is not disordered not only before drying but also after drying. Moreover, the diffraction wavelength based on the crystal structure is in the visible region, so the incident light is diffracted and the structural color is observed. In contrast, in Comparative Example 1, the crystal structure is disordered due to drying, the diffraction is incomplete, and the structural color disappears.
[0137] However, in the dried crystals, the medium surrounding the particles is not water (refractive index nr = 1.33) but PDMA (DMA monomer nr = 1.47), which is close to the refractive index of silica (nr = 1.43). Therefore, the color after drying in Example 1 becomes weaker than that before drying.
[0138] (Example 3)
[0139] In Example 3, the dried immobilized two-dimensional colloidal crystals were further firmly immobilized by photopolymerization of DMA monomers.
[0140] That is, a silicon wafer with a 2 cm square hole is placed on a substrate to form a recess. After immobilized colloidal crystals are made in the recess in the same manner as in Example 1 (however, the concentration of PDMA is set to 0.25 wt.%, and the amount dropped into the recess is set to 1.5 mL), 600 μL of a liquid in which VA-086 (Wako Pure Chemical Industries, Ltd.) as a photoradical polymerization initiator is dissolved in dimethylacrylamide (DMA) monomer at a concentration of 6.67 mg / mL is added to the recess, and after UV irradiation to photopolymerize DMA, the DMA is heated in an oven at 80 to 100°C to evaporate the unreacted DMA monomer. In this way, the dried immobilized two-dimensional colloidal crystals of Example 1 are further fixed and strengthened with a PDMA resin having a thickness of about several mm. The results are as shown below. Fig.11(a) shows the structural color. In addition, microscopic observation shows that the crystal structure remains unchanged ( Fig.11 (b)). It should be noted that the average inter-particle distance was 1.59±0.01 μm.
[0141] In addition, for the immobilized two-dimensional colloidal crystals of Example 1, the structure of the two-dimensional colloidal crystals was evaluated by laser diffraction (a schematic diagram of the apparatus used in the laser diffraction method is shown in FIG. Fig.12 The laser (helium-neon laser) was scattered in a cone shape on the light diffusion plate to irradiate the fixed two-dimensional colloidal crystal of Example 2, and the diffraction pattern was projected on a screen set on the lower surface of the glass block. Then, the diffraction pattern was observed using an optical reflector and photographed using a camera. The result is shown in FIG. Fig.13 As shown, diffraction spots derived from the six-fold symmetric crystal structure were clearly confirmed.
[0142] <Isolation of two-dimensional colloidal crystals with a 4-fold symmetric crystal structure>
[0143] (Example 4)
[0144] In Example 4, a two-dimensional colloidal crystal having a crystal structure with four-fold symmetry was produced by crystallizing the colloidal crystal in a narrow gap with a controlled spacing.
[0145] First, a cell was prepared as a cell for crystallizing colloidal crystals. Fig.14 A colloidal crystal preparation pool 30 is shown. This pool is a 5 mm thick silicon wafer 32 having a 2 cm × 2 cm square hole bonded to a glass substrate 31 surface-modified with 3-aminopropyltrimethoxysilane. In addition, a colloidal crystal dispersion consisting of an alkaline silica dispersion mixed with 100 μl of silica particles d = 1000 nm (KE-P100, 28 vol.%) and 70 μl of NaOH (0.01 M) is prepared. The colloidal crystal dispersion is dripped onto the surface-modified glass substrate 31, covered with a plastic plate 33 from above, and a glass block 34 and a weight 35 are placed above the plastic plate 33. By changing the weight of the weight 35, the spacing of the gap formed by the glass substrate 31 and the plastic plate 33 is adjusted. The colloidal crystal dispersion is considered to be alkaline, so the amino groups modifying the glass substrate are not ionized, and the surface charge of the glass substrate becomes negative due to the silanol groups on the glass surface. The surface charge of the silica particles also becomes negative, so the silica particles are not adsorbed to the glass substrate.
[0146] Next, an ion exchange resin is added to the gap between the plastic plate 33 and the colloidal crystal preparation pool 30 and left for 3 days. Thus, the alkali in the colloidal crystal dispersion is removed by ion exchange. Therefore, the amino groups on the surface of the glass substrate 31 are ionized, and the surface charge is positive, so the colloidal crystals composed of silica particles with negative surface charge are adsorbed on the glass substrate 31.
[0147] Then, use Milli-Q water to rinse the excess colloidal crystal dispersion and ion exchange resin. Fig.15 A microscope photograph of the glass substrate 31 obtained in this way is shown. From this photograph, it can be seen that a two-dimensional colloidal crystal having a crystal structure with four-fold symmetry is formed on the glass substrate 31. The average interparticle distance of this two-dimensional colloidal crystal is 1.28 μm.
[0148] Then, PDMA was further added at 1.25 mg / cm 2 The immobilized two-dimensional colloidal crystals were obtained by adding the two-dimensional colloidal crystals in a ratio of 1:1 and drying the two-dimensional colloidal crystals (the operation is the same as in Example 3 and the description is omitted). When the immobilized two-dimensional colloidal crystals obtained in this way were observed under an optical microscope, as shown in FIG. Fig.16 As shown, it can be seen that the four-fold symmetric crystal structure before immobilization is not disturbed but remains unchanged.
[0149] <Isolation of two-component two-dimensional colloidal crystals having a crystal structure with four-fold symmetry>
[0150] (Example 5)
[0151] In Example 5, a two-dimensional colloidal crystal composed of two types of colloidal particles and having a crystal structure with four-fold symmetry was prepared and immobilized.
[0152] First, two-dimensional colloidal crystals with a crystal structure having four-fold symmetry before immobilization with PDMA were prepared by the same method as in Example 4. Then, about 1 mL of water was left in the colloidal crystal preparation pool 30, and 100 μL of a dispersion of colored silica particles (particle size 500 nm, green fluorescent color) was added to the pool, gently stirred, and left to stand for 24 hours. After the colloidal crystals were adsorbed on the glass substrate 31 in this way, an ion exchange resin was added to the gap between the plastic plate 33 and the colloidal crystal preparation pool 30, and after being left for 3 days, they were observed from the back side of the glass substrate 31 using an optical microscope.
[0153] The results are shown in Fig.17 . Fig.17 (a) and (b) are microscope photos of the same field of view. Fig.17 (c) Yes Fig.17 (a) and Fig.17 (b) (the first component is colored red). Fig.17(d) is a microscope photograph of another field of view. The average inter-particle distance is equal to 1.38 μm for the silica particles of the first component and the silica particles of the second component.
[0154] From the above results, it can be seen that the two-dimensional colloidal crystal with a crystal structure having a four-fold symmetry composed of the first component adsorbed on the glass substrate 31 and the two-dimensional colloidal crystal with a crystal structure having a four-fold symmetry composed of the second component are formed by staggered positions, and the colloidal particles of the second component are located in the center of the lattice formed by the colloidal particles of the first component.
[0155] Then, according to the same method as in Example 1, PDMA (addition amount: 1.25 mg / cm 2 ) immobilized two-dimensional colloidal crystals consisting of two components, and the results of microscopic observation from the back side of the glass substrate 31 are as follows: Fig.18 As shown, it can be seen that based on the crystal structure before PDMA immobilization (refer to Fig.17 ) remains unchanged.
[0156] <Isolation of two-component two-dimensional colloidal crystals having a crystal structure with six-fold symmetry>
[0157] (Examples 6-1, 6-2 and Comparative Example 1)
[0158] In Examples 6-1 and 6-2 and Comparative Example 1, two-dimensional colloidal crystals composed of two types of colloidal particles and having a crystal structure with six-fold symmetry were prepared and immobilized.
[0159] First, according to the method of Example 1, colloidal crystals of silica particles (KE-P100, d=1060nm) were fixed to a substrate to produce a two-dimensional colloidal crystal having a component of a crystal structure with six-fold symmetry (however, in Example 6-1, the concentration of silica particles in the silica particle aqueous dispersion was 6vol.%, in Example 6-2, it was 9vol.%, and in Comparative Example 1, it was 0.5vol.%). Next, 100μL of an aqueous dispersion of silica particles dyed with green fluorescent dye (Micromod, Sicastar 500, d=467nm) was added, gently stirred, and allowed to stand for 24 hours. Then, the glass substrate 31 was observed from the back with a fluorescence microscope. The results of Example 6-1 are shown in Fig.19 In this fluorescence microscope observation, only the particles of the second component (i.e., silica particles with an average particle size of 467 nm dyed with green fluorescent dye) are observed as bright circles, and the particles of the first component (i.e., silica particles with an average particle size of 1060 nm not dyed with fluorescent dye) are observed as black circles. Fig.19It can be seen that silica particles with an average particle size of 467 nm, which are the second component, are arranged between silica particles with an average particle size of 1060 nm, which are the first component. The center-to-center distance between the silica particles of the first component is 1.67 μm.
[0160] When the same fluorescence microscope observation was performed on Example 6-2 and Comparative Example 1, the same crystal structure as that of Example 6-1 was observed in Example 6-2, and the center-to-center distance of the silica particles of the first component was 1.55 μm. However, in Comparative Example 1, the same crystal structure as that of Example 6-1 was not observed, and a plurality of silica particles of the second component existed between the particles of the first component, and no clear lattice was observed. In addition, the center-to-center distance of the silica particles of the first component was 1.78 μm.
[0161] From the above results, it can be seen that by appropriately adjusting the dispersion concentration of the silica particles in the silica particle aqueous dispersion of the first component, the distance between the silica particles of the first component can be controlled. Then, by further appropriately adjusting the dispersion concentration of the silica particles in the silica particle aqueous dispersion of the first component, a two-dimensional colloidal crystal having a crystal structure with a six-fold symmetry composed of the first component adsorbed on the glass substrate 31 can be formed, and at the same time, a crystal structure having a six-fold symmetry composed of the second component can be formed.
[0162] In Example 6-1, PDMA (addition amount: 1.25 mg / cm 2 ) The two-dimensional colloidal crystal composed of two components was fixed and observed from the back of the glass substrate 31 by fluorescence microscope. The results are as follows Fig. 20 As shown, it can be seen that based on the crystal structure before PDMA immobilization (refer to Fig.19 ) remains unchanged.
[0163] <Immobilization of two-dimensional colloidal crystals using styrene resin>
[0164] (Example 7)
[0165] In Example 7, the two-dimensional colloidal crystals were fixed by a styrene resin. This will be described in detail below.
[0166] The substrate preparation step, colloidal crystal dispersion preparation step, colloidal crystal adsorption step, and cleaning step were performed in the same manner as in Example 1, and the recess was cleaned with Milli-Q water until about 200 μL of Milli-Q water remained.
[0167] ·Styrene monomer solution adjustment process
[0168] A monomer solution composed of 95 wt% styrene monomer and 5 wt% ethylbenzene was stirred while being kept at room temperature. Furthermore, 0.21×10 -3 mol / L of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, and stirred to obtain a styrene monomer solution containing a polymerization initiator.
[0169] Immobilization process
[0170] 500 μL of a styrene monomer solution containing a polymerization initiator was added to the concave portion and mixed with a pipette. Then, the mixture was dried in an oven at 145°C for 1 hour to evaporate the water, and observations were performed with the naked eye and an optical microscope. The results showed the same structural color as in Example 1, indicating that the crystal structure was an immobilized two-dimensional colloidal crystal with a 6-fold symmetry.
[0171] <Immobilization of two-dimensional colloidal crystals using (meth)acrylic resin>
[0172] (Example 8)
[0173] In Example 8, trimethylolpropane triacrylate was used as the (meth)acrylic resin to fix the two-dimensional colloidal crystals. This will be described in detail below.
[0174] The substrate preparation step, colloidal crystal dispersion preparation step, colloidal crystal adsorption step and cleaning step were performed in the same manner as in Example 1, and the recessed portion was cleaned with Milli-Q water until about 200 μL of Milli-Q water remained.
[0175] ·(Meth)acrylic resin solution adjustment step
[0176] The (meth)acrylic resin solution having the following mixing ratio was kept at room temperature and stirred.
[0177] Trimethylolpropane triacrylate: 90 parts by weight,
[0178] Pentaerythritol tetrakis(3-mercaptobutyrate) 1: 10 parts by weight
[0179] Irgacure 184: 2 parts by weight
[0180] Immobilization process
[0181] 500 μL of the (meth) acrylic resin solution was added to the concave portion and mixed with a pipette. After further irradiation with UV for photopolymerization, the solution was dried in an oven at 100°C for 1 hour to evaporate the water, and observations were performed with the naked eye and with an optical microscope. The results showed the same structural color as in Example 1, indicating that the solution was an immobilized two-dimensional colloidal crystal with a crystal structure having a six-fold symmetry.
[0182] <Immobilization of two-dimensional colloidal crystals using PEG and poly(vinylmorpholine)>
[0183] (Example 9)
[0184] In Example 9, two-dimensional colloidal crystals were immobilized by polyethylene glycol (PEG) and polyvinylmorpholine. This will be described in detail below.
[0185] In the same manner as in Example 1, a substrate preparation step, a colloidal crystal dispersion preparation step, a colloidal crystal adsorption step, and a cleaning step were performed to prepare a two-dimensional silica colloidal crystal having a crystal structure with six-fold symmetry (see Fig.21 (a)).
[0186] Immobilization process
[0187] The immobilization step was performed in two steps, namely, first immobilization using polyethylene glycol and then further immobilization using polyvinylmorpholine.
[0188] That is, first, 50 μL of an aqueous solution of polyethylene glycol (PEG, molecular weight 35,000, 3 wt%) was added to the concave portion and mixed with a pipette. The concentration of the PEG aqueous solution was adjusted to 1.5 mg / cm 2 Furthermore, the immobilized two-dimensional colloidal crystals were obtained by drying in an oven at 40°C overnight to evaporate the water (refer to Fig.21 (b)).
[0189] After N-vinylmorpholine was aerated with nitrogen for 1 minute, 500 μL of a solution to which VA086 as a photopolymerization initiator was added was added to make it 0.5 mg / ml in each pool, and UV light was irradiated for 1 hour for fixation. Microscopic observation after photocuring showed that the structure of the two-dimensional crystal with a 6-fold symmetry crystal structure remained intact (refer to Fig.21 (c)). It should be stated that Fig.21 Each side of the photographs (a), (b), and (c) is 26 μm.
[0190] (Example 10)
[0191] In Example 10, PEG with a molecular weight of 100,000 was used in the immobilization step. The other operations were the same as those in Example 9. Microscopic observation after PEG immobilization revealed that a two-dimensional colloidal crystal having a crystal structure with six-fold symmetry was formed (see Fig. 22 (a)). In addition, microscopic observation after photocuring showed that the structure of the two-dimensional crystal with a six-fold symmetry remained unchanged (refer to Fig. 22 (b)). It should be noted that Fig. 22 In the photos (a) and (b), each side is 26 μm.
[0192] <Immobilization of two-dimensional colloidal crystals using Pluronic(registered trademark)>
[0193] (Example 11)
[0194] In Example 11, polystyrene particles were used as colloidal particles, and in the immobilization step, Pluronic (registered trademark) (ie, a triblock copolymer of polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol) was used for immobilization.
[0195] Substrate preparation process
[0196] In the same manner as in Example 1, the surface of the cover glass was modified with aminopropyl, and then a plastic frame of 8 connected cells (each cell was a square of 1 cm×1 cm) was bonded thereto.
[0197] ·Colloidal crystal dispersion preparation process
[0198] A 10 vol% aqueous dispersion of polystyrene particles (diameter 430 nm, model No. 5043B, Thermo Corporation) was prepared and desalted by adding ion exchange resin (AG501-X8(D) from BioRad Corporation, 20-50 sieve) to obtain an aqueous dispersion of three-dimensional charged colloidal crystals of polystyrene particles regularly arranged in water due to electrostatic repulsion.
[0199] The colloidal crystal adsorption process and the cleaning process are the same as those in Example 1.
[0200] The optical microscope photograph after cleaning is shown in Fig.23 (a) From this photograph, it can be seen that a two-dimensional colloidal crystal having a crystal structure with six-fold symmetry is formed.
[0201] Immobilization process
[0202] 394 μL of an aqueous solution of Pluronic (registered trademark) (molecular weight 8,400, ALDRICH) at a concentration of 3.165 mg / mL was added to the cell, and the cell was placed in an oven at 40° C. to dry for 2 days.
[0203] Microscopic observation after immobilization revealed that immobilized two-dimensional colloidal crystals with a six-fold symmetric crystal structure were formed (refer to Fig.23 (b)).
[0204] In the immobilized two-dimensional colloidal crystal of Example 11, hydrophobic polystyrene particles are used as colloidal particles, and hydrophilic glass is used for the substrate. In addition, Pluronic (registered trademark) used for immobilization has a polyethylene glycol chain composed of hydrophilicity and a polypropylene glycol chain composed of hydrophobicity. Therefore, the polypropylene glycol chain is adsorbed on the surface of the hydrophobic polystyrene particles, and the polypropylene glycol chain is adsorbed on the glass surface of the hydrophilic substrate, and the two-dimensional colloidal crystal composed of the polystyrene particles is firmly immobilized on the substrate surface via Pluronic (registered trademark).
[0205] (Example 12)
[0206] In Example 12, an aqueous solution of Pluronic (registered trademark) (ALDRICH) with a molecular weight of 14600 (concentration 3.185 mg / mL) was used in the immobilization step. Other operations and conditions were the same as those in Example 11. Microscopic observation after immobilization revealed that a two-dimensional colloidal crystal having a crystal structure with six-fold symmetry was formed (see Fig.24 ).
[0207] <Immobilization of two-dimensional colloidal crystals composed of polystyrene particles>
[0208] (Example 13)
[0209] In Example 13, immobilization of two-dimensional colloidal crystals was performed using polystyrene particles instead of silica particles. This will be described in detail below.
[0210] The substrate preparation step was carried out in the same manner as in Example 1.
[0211] ·Colloidal crystal dispersion preparation process
[0212] An aqueous dispersion of polystyrene particles with a diameter of 1000 nm (Thermo Company, coefficient of variation of particle size = 2.2%, negative charge) was concentrated to a 6 vol.% aqueous dispersion, and ion exchange resin (BioRad Company AG501-X8(D), 20-50 mesh) was added for desalination to obtain an aqueous dispersion of three-dimensional charged colloidal crystals in which the polystyrene particles were regularly arranged in water due to electrostatic repulsion.
[0213] The colloidal crystal adsorption step, washing step, and immobilization step were performed in the same manner as in Example 1. The obtained solidified body was observed with the naked eye and with an optical microscope, and the result showed the same structural color as in Example 1, indicating that it was an immobilized two-dimensional colloidal crystal having a crystal structure with six-fold symmetry.
[0214] The present invention is not limited to the above-mentioned embodiments and examples, but includes various modifications that can be easily conceived by those skilled in the art without departing from the scope of the claims.
[0215] The two-dimensional colloidal crystal of the present invention is very suitable for use as a functional surface in sensing, photonics, plasmon optics, etc. because its crystal structure is not easily disordered.
[0216] Explanation of symbols
[0217] S1, S11, S21...substrate preparation process,
[0218] S2, S12 ... colloidal crystal dispersion preparation process,
[0219] S22: a first colloidal crystal dispersion preparation step,
[0220] S3, S13 ... colloidal crystal adsorption step, S23 ... first colloidal crystal adsorption step, S25 ... second colloidal particle dispersion preparation step,
[0221] S26 ... a second colloidal crystal adsorption step, S4, S14, S24, S27 ... a cleaning step,
[0222] S5, S15, S28...fixation process,
[0223] 5a, 5b, 11, 21 ... substrate, 12 ... counter plate, 2, 13, 22, ... colloidal particles,
[0224] 23 ... second colloidal particles, 14, 24 ... resin, 6 ... charged colloidal dispersion liquid, 7 ... charge preparation liquid.
Claims
1. An immobilized two-dimensional colloidal crystal, wherein the colloidal crystal consisting of a single layer is immobilized by a resin.
2. The immobilized two-dimensional colloidal crystal according to claim 1, wherein: The colloidal crystals are formed on a substrate.
3. The immobilized two-dimensional colloidal crystal according to claim 2, wherein: The substrate is a light-transmitting substrate.
4. The immobilized two-dimensional colloidal crystal according to any one of claims 1 to 3, wherein The resin is an acrylic resin or a styrene resin.
5. The immobilized two-dimensional colloidal crystal according to claim 4, wherein: The resin is polydialkyl acrylamide.
6. The immobilized two-dimensional colloidal crystal according to any one of claims 1 to 3, wherein The colloidal particles constituting the colloidal crystals are silicon dioxide or polystyrene.
7. The immobilized two-dimensional colloidal crystal according to claim 3, wherein: The value of the refractive index of the resin / the refractive index of the light-transmitting substrate is in the range of 0.9 to 1.
1.
8. The immobilized two-dimensional colloidal crystal according to any one of claims 1 to 3, wherein The colloidal crystal is composed of a variety of colloidal particles.
9. The immobilized two-dimensional colloidal crystal according to any one of claims 1 to 3, wherein The colloidal crystal has a crystal structure with 4-fold symmetry or 6-fold symmetry.
10. A method for producing immobilized two-dimensional colloidal crystals, comprising: A substrate preparation step of preparing a substrate having a surface charge; a colloidal crystal dispersion preparation step of preparing a charged colloidal crystal dispersion in which three-dimensional colloidal crystals composed of colloidal particles having a surface charge of opposite sign to the surface charge of the substrate are dispersed in a dispersion medium; a colloidal crystal adsorption step of bringing the charged colloidal crystal dispersion into contact with the substrate to adsorb the colloidal crystals on the substrate; a cleaning step of cleaning the substrate on which the colloidal crystals are adsorbed with a cleaning solution to form a two-dimensional colloidal crystal consisting of a single layer on the substrate; and In the fixing step, the substrate on which the two-dimensional colloidal crystal is formed is brought into contact with a resin solution, and then the two-dimensional colloidal crystal is fixed by drying the resin solution.
11. The method for producing immobilized two-dimensional colloidal crystals according to claim 10, wherein: After the cleaning process, a second colloidal particle adsorption process is performed to bring the substrate formed with the two-dimensional colloidal crystal into contact with a second colloidal particle dispersion in which second colloidal particles of a type different from the colloidal particles are dispersed in a dispersion medium, and a cleaning process is performed to clean the substrate adsorbed with the second colloidal particles, and then the immobilization process is performed.
12. The method for producing immobilized two-dimensional colloidal crystals according to claim 10 or 11, wherein: After the immobilization step, the polymerizable monomer is further polymerized on the immobilized two-dimensional colloidal crystal.
13. A two-dimensional colloidal crystal, wherein a plurality of colloidal particles form a colloidal crystal consisting of a single layer.
14. The two-dimensional colloidal crystal according to claim 13, wherein: The colloidal crystal has a crystal structure with 4-fold symmetry or 6-fold symmetry.
15. The method for producing a two-dimensional colloidal crystal according to claim 13 or 14, characterized in that: Carry out the following process: A substrate preparation step of preparing a substrate having a surface charge; a colloidal crystal dispersion preparation step of preparing a charged colloidal crystal dispersion in which three-dimensional colloidal crystals composed of first colloidal particles having a surface charge having a sign opposite to that of the surface charge of the substrate are dispersed in a dispersion medium; a colloidal crystal adsorption step of bringing the charged crystal dispersion into contact with the substrate to adsorb the colloidal crystals on the substrate; A cleaning step of cleaning the substrate on which the colloidal crystals are adsorbed with a cleaning solution to form a two-dimensional colloidal crystal consisting of a single layer on the substrate; a colloidal particle adsorption step of bringing the substrate on which the two-dimensional colloidal crystal is formed into contact with a colloidal particle dispersion in which second colloidal particles different in type from the first colloidal particles are dispersed in a dispersion medium after the cleaning step; and The second cleaning step is to clean the substrate on which the second colloidal particles are adsorbed.
Citation Information
Patent Citations
SPR measurement substrate and manufacturing method therefor
JP2020034543A